Cooperative societies as sources of health insurance among members in Ibadan, Nigeria (2022)
Cooperative societies are noted for addressing members ’ social and economic needs, but they are yet to channel their resources towards meeting members ’ health care needs. This study investigated the role of cooperative societies in accessing health care Services for poor urban members in Ibadan metropolis, Oyo State, Nigeria. Cross-sectional survey was conducted among 480 members of cooperative societies in Ibadan metropolis using a semi-structured questionnaire and Key Informants Interviews consisting of three (3) presidents of the organization. Face validity was employed for the questionnaire and internal consistency reliability was determined. Purposive sampling technique was used in selecting respondents and participants for the study. Triangulation technique was adopted in which descriptive statistic was used to measure the perceived effectiveness of cooperative society in members ’ health care and thematic approach used to analyse the qualitative data. Result reveals that members of cooperatives are all interested and are looking forward to when health care scheme will be introduced to the` activities of cooperative society. It was concluded that cooperative societies can be utilised to enhance health condition of co- operators and necessary recommendations were made